Copper and Zinc Co-doped Titanium Dioxide Nanotubes Arrays on Controlling Nitric Oxide Releasing and Regulating the Inflammatory Responses for Cardiovascular Biomaterials - Yin, Benli; Luo, Xiao; Gao, Peng Y.; Jiao, Zhi Sha; Piao, Jun Ji; Zhao, An Sha; Yang, Ping (Recent Patents on Nanotechnology, 2023)
Background: Titanium dioxide (TiO2) nanotubes arrays have shown tremendous application foreground due to their unique characters of structure and performance. However, the single bio-function is still the limit on cardiovascular biomaterials. Methods: The loadability function provides the possibility for the TiO2 nanotubes arrays to realize composite multifunction. The copper can catalyze the release of nitric oxide to promote the proliferation of endothelium cells and improve the anticoagulant. Also, zinc can adjust the inflammatory responses to improve anti-inflammation. Results: In this patent work, we co-doped the copper and zinc onto TiO2 nanotubes arrays to estimate the hemocompatibility, cytocompatibility and responses of inflammation. The results showed that copper and zinc could introduce better multi-biofunctions to the TiO2 nanotubes arrays for the application in cardiovascular biomaterials. Conclusion: In summary, the NTs@Cu/Zn sample as a new composite material in this study had significant biocompatibility in vascular implantation and can be used as a potential material for polymer- free drug-eluting stents.
Keywords: hemocompatibility